Planning FKUB Dalam Mewujudkan Kerukunan Ummat Pasca Konflik Keagamaan Di Kota Tanjung Balai Tahun 2016 - Surya, Muhammad; Efendi, Erwan (Universitas Cokroaminoto Yogyakarta, 2025)
This qualitative research explains the role of the Forum for Religious Harmony (FKUB) planning in building religious harmony in Tanjung Balai City after the 2016 conflict. Data collection through interviews, participant observation, and documentation. The results show that FKUB's planning includes increasing consolidation and partnership dialogue between religious communities, periodic coordination with local government in socialization of religious harmony. Efforts for moderation religion are also demonstrated through the development of an integrative religious tourism area of ​​six places of worship from various religions. FKUB Tanjung Balai serves as a communication mediator between religious communities, organizes joint activities, and conducts socialization to enhance tolerance. Tanjung Balai's status as an intolerant city has changed into a model for religious harmony. Systematic and participatory FKUB planning is the key to building tolerance and harmony between religious communities.